Fundamentals and evolution of MPEG-2 systems paving the MPEG road - Meer, Jan van der (Electrical engineer) (Chichester, West Sussex, United Kingdom : Wiley, 2014)
"This book examines the MPEG-2 system specification as developed in the early 1990's, as well as its evolution into the fourth edition of the MPEG-2 systems standard, published in 2013"--
11.12 Program Stream Carriage within a Transport Stream11.13 PES Streams; 11.14 Room for Future Extensions; References; Chapter 12: The MPEG-2 System Target Decoder Model; 12.1 Introduction to the MPEG-2 STD; 12.2 The Program Stream STD: P-STD; 12.3 Transport Stream STD: T-STD; 12.4 General STD Constraints and Requirements; 12.5 Content Format Specific STD Issues; Chapter 13: Data Structure and Design Considerations; 13.1 System Time Clock Samples and Time Stamps; 13.2 PES Packets; 13.3 Descriptors of Programs and Program Elements; 13.4 Program Streams; 13.5 Sections
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: MPEG (Video coding standard); MPEG (Video coding standard); TECHNOLOGY & ENGINEERING -- Telecommunications; MPEG (Video coding standard); MPEG (Video coding standard); Electronic books